Laptops in the long-run: Evidence from the one laptop per child program in rural Peru - Santiago Cueto; Diether W. Beuermann; Julian Cristia; Ofer Malamud; Francisco Pardo (Inter-American Development Bank (IDB), 2024)
This paper examines a large-scale randomized evaluation of the One Laptop Per Child (OLPC) program in 531 rural primary schools, as implemented by the Peruvian government starting in 2009. We use administrative and survey data on academic achievement and grade progression through 2019 to estimate the long-run effects of educational technology on i) academic performance and grade progression in schools over time and ii) student trajectories as they progress from primary school to university. We find negative and significant effects on completing primary and secondary education on time but no effects on achievement. We find positive and significant impacts on students' computer skills but no effects on broader cognitive skills. Information on teacher training and computer utilization suggests limited benefits of providing educational technology without sufficient pedagogical support.
Keywords: I21; I24; I28; 330; Education; Technology; Evaluation